Green policy effect on firm sustainability: examining the stock performance of ESG adopters in heavy-polluter industry in Malaysia - Norhamiza Ishak; Nazliatul Aniza Abdul Aziz; Fithriah Ab Rahim (Informa UK Limited, trading as Taylor & Francis Group, 2024)
This study aims to investigate the effect of the green policy announcement on heavy-polluter stock returns in Malaysian industries. The study adopted a market-model event study methodology to measure 251 heavy-polluter companies from October 9, 2009 to October 29, 2021. Based on the findings, the first objective (to accept H1) showed that investors in Malaysia demonstrated mixed reactions (+ve and –ve) towards the green policy announcement whereas the second objective (to accept H2) revealed that there is an effect (+ve and –ve) for ESG adopters in three industries namely chemical and construction, metal and mining, and travel and leisure towards the green policy announcement. From a practical standpoint, there are several implications to consider. Firstly, investors, portfolio managers, and regulators can utilize stock returns as a means to maximize shareholders’ wealth. Secondly, the incorporation of ESG practices in the selection of companies can serve as a performance indicator for investment decisions. Thirdly, government entities can benefit from the ratification of green policies as an effective approach towards maximizing shareholders’ value. A theoretical perspective, an efficient market, investors cannot generate abnormal profits once the announcement is made. Failure to incorporate information related to environmental events into share prices would be inconsistent with the efficient market hypothesis. Finally, from a management or company standpoint, investing in green initiatives allows heavy-polluter companies to transition into more energy-efficient and environmentally friendly entities, fulfilling their social, environmental, and ESG responsibilities. This study’s novelty focuses on the relationship between stock performance, green finance policies, and ESG adoption.